Islamic Plurality in the Perspectives of Ulama Dayah in Aceh - Syarifuddin, Syarifuddin (Jurnal Ilmiah Peuradeun, 2021)
This study aimed to explain the views of Ulama Dayah on the plurality of Acehnese society. The Acehnese, especially the Ulama Dayah (Teungku) are community leaders for the people of Aceh. Ulama Dayah welcome the concept of plurality in the sense of tolerance which they consider sunnatullah. However, if plurality causes disturbance to religious practice in society, it will be rejected, especially if it is contrary to the Ahlussunnah wal Jamaah doctrine which is oriented to the Shafi'i school. This research used a qualitative method with a descriptive-analytic approach. The subjects of this research were the ulama who graduated from dayah represented 12 organizations that manage the dayah community. This study did not specify which areas would be studied, because the data were taken based on interviews with 3 Ulama Dayah representing the dayah community organization. The research procedure was carried out in four steps: observation, in-depth interviews, and documentation. The data were analyzed using an inductive model. The results of the study were as follows; First, the impact of Ulama Dayah’s thought on plurality in Islamic schools of thought was very important. Second, the role of Ulama Dayah as a reference has actually existed since the days of the Aceh Sultanate. Third, the influence of Ulama Dayah thoughts was also strongly influenced by the number of worshipers. Finally, institutionally, the existence of the Dayah Education Office in Aceh was a liaison between the dayahs and the government in equalizing public perceptions.